ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH DI KELURAHAN BUBUTAN KOTA SURABAYA - Mustofa, Muhammad Ali; Arief, Sjamsul (JEB17 : Jurnal Ekonomi dan Bisnis, 2021)
Micro, small and medium enterprises (MSMEs) are business activities that can expand job opportunities and provide various kinds of economic services to the community, as well as play a role in equitable distribution and increase in community income, encourage economic growth and achieve national economic stability. There are many types of businesses that can be carried out, both in the food, beverage and other sectors. The role of Micro, Small and Medium Enterprises (MSMEs) in the national economy is very large. The economic crisis that was preceded by the monetary crisis that occurred in Indonesia showed that MSMEs were relatively more resilient in facing this crisis, than large-scale businesses which often went bankrupt. The income of traders is influenced by various factors. This study uses the following variables: capital, labor and length of business. This study aims to determine the effect of capital, labor and duration of business for the income of micro, small and medium enterprises in Bubutan Village.     Methods. Primary data collection was carried out by stratified random sampling method. The study took 30 respondents as samples. The analysis uses multiple linear regression with income as the dependent variable and three independent variables, namely capital (X1), labor (X2) and length of business (X3). The results of the classic assumption of deviations show that the data is normally distributed and there are no deviations. Based on the calculation of SPSS 25, the F value is 6,368 with ? significance of 0.002b. By using a significance of 0.05 obtained F Table (4. 9), then the value of F (6.368)> F Table (4. 9) or the significance of F of 0.002b indicates less than 0.05 so it can be concluded that the four independent variables namely capital (X1), labor (X2) and length of business (X3) together affect the amount of income received by micro, small and medium enterprises in Bubutan Village. Partly, with the variable initials capital (X1), labor (X2) and length of work (X3).